Climate-Smart Agriculture In Benin: Need Assessment Report - Assogbadjo, Achille E; Avakoudjo, Hospice G; Bonou, Alice; Djagoun, Chabi A; Avocevou-Ayisso, Carolle; Chadare, Flora J. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Agriculture in Africa must undergo a major transformation in the coming decades in order to meet the interrelated challenges of achieving food security, reducing poverty, and addressing climate change without depleting the natural resource base. Although agriculture is an important part of Africa's economy, employing more than 60% of the population and contributing between 25% and 34% of GDP, productivity is low and food insecurity is high. Currently, about 48% of Africa's population, or approximately 450 million people, live in extreme poverty on less than US$1.25 per day; 63% of the continent's poor live in rural areas and depend on agriculture for their livelihoods (World Bank, 2015). At the same time, the continent is experiencing rapid population growth and urbanization. Half of the projected 2.4 billion increase in the world's population between 2013 and 2050 will occur in sub-Saharan Africa (SSA), and 56 percent of Africa's population is expected to live in urban areas by 2025 (UNODAES, 2013 and 2014). Meeting future food demand will require a large increase in supply. With these challenges, agricultural practices on the African continent cannot continue as usual. African agriculture must therefore transform itself to improve food and nutrition security for an expanding population and to provide a basis for economic growth and poverty. reduction.